Removal of phenol from wastewater using spiral-wound reverse osmosis process: Model development based on experiment and simulation. (August 2017) - Al-Obaidi, M.A.; Kara-Zaïtri, C.; Mujtaba, I.M.
Highlights: The feasibility of mitigating phenol concentration of industrial effluents by RO. A new model is developed for a spiral-wound RO process based phenol rejection. The model predicts the operating conditions along two sides of the membrane length. gEST tool in gPROMS used to estimate the membrane transport and friction parameters. Abstract: The removal of the ubiquitous phenol and phenolic compounds in industrial wastes is a critical environmental issue due to their harmful threats to wildlife and potential adverse human health effects. The removal of such compounds is therefore of significant importance in water treatment and reuse. In recent years, reverse osmosis (RO) has been successfully utilised in several industrial processes and wastewater treatment including phenol removal. In this paper, a new model based on a spiral-wound RO process is developed for the removal of phenol from wastewater. A simplified mathematical algorithm using an irreversible thermodynamic approach is developed. This results in a set of non-linear Differential and Algebraic Equations (DAEs), which are solved based on a number of optimised model parameters using a combined methodology of parameter estimation and experimental phenol-water data derived from the literature. The effects of several operational parameters on the performance (in terms of removal of phenol) of the process are explored using the model.